2017
DOI: 10.1155/2017/9012929
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Classical Formula Sijunzi Decoction and Chronic Atrophic Gastritis: Evidence for Treatment Approach?

Abstract: Objective This aim is to evaluate the effect of Sijunzi decoction (SJZD) treating chronic atrophic gastritis (CAG). Methods We performed searches in seven databases. The randomized controlled trials (RCTs) comparing SJZD with standard medical care or inactive intervention for CAG were enrolled. Combined therapy of SJZD plus conventional therapies compared with conventional therapies alone was also retrieved. The primary outcome included the incidence of gastric cancer and the improvement of atrophy, intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Sijunzi decoction, a traditional Chinese herbal formula, has been widely used to treat gastrointestinal disorders. Several meta-analyses demonstrated that Sijunzi decoction was efficacious and safe for atrophy chronic gastritis and gastric cancer [24,30]. Clinical studies have shown that Sijunzi decoction or modified Sijunzi decoction can reverse pathological gastric changes (including chronic atrophic gastritis, intestinal metaplasia, and gastric epithelial dysplasia) and is effective in treating patients with fatigue and tiredness [24][25][26]31].…”
Section: Clinical Effects Of Tcms On Gplmentioning
confidence: 99%
See 1 more Smart Citation
“…Sijunzi decoction, a traditional Chinese herbal formula, has been widely used to treat gastrointestinal disorders. Several meta-analyses demonstrated that Sijunzi decoction was efficacious and safe for atrophy chronic gastritis and gastric cancer [24,30]. Clinical studies have shown that Sijunzi decoction or modified Sijunzi decoction can reverse pathological gastric changes (including chronic atrophic gastritis, intestinal metaplasia, and gastric epithelial dysplasia) and is effective in treating patients with fatigue and tiredness [24][25][26]31].…”
Section: Clinical Effects Of Tcms On Gplmentioning
confidence: 99%
“…Several meta-analyses demonstrated that Sijunzi decoction was efficacious and safe for atrophy chronic gastritis and gastric cancer [24,30]. Clinical studies have shown that Sijunzi decoction or modified Sijunzi decoction can reverse pathological gastric changes (including chronic atrophic gastritis, intestinal metaplasia, and gastric epithelial dysplasia) and is effective in treating patients with fatigue and tiredness [24][25][26]31]. Weiansan, a classical formula commonly used in the treatment of GPL, was found to have definite effects, including suppression of glandular atrophy, intestinal metaplasia, and dysplasia and elimination of H. pylori [17].…”
Section: Clinical Effects Of Tcms On Gplmentioning
confidence: 99%
“…It was used to treat various digestive diseases such as gastritis, duodenitis, and inflammatory bowel disease [ 8 ]. As for chronic gastritis, researchers have conducted some clinical trials to investigate the effects of Sijunzi decoction [ 9 ]. Tian et al found that modified Sijunzi decoction could alleviate the symptoms of chronic atrophic gastritis such as fatigue and tiredness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al found that modified Sijunzi decoction could alleviate the symptoms of chronic atrophic gastritis such as fatigue and tiredness [ 10 ]. Gan et al enrolled 6 randomized controlled trials to conduct meta-analysis and demonstrated that Sijunzi decoction was beneficial to chronic atrophic gastritis patients [ 9 ]. However, they have not revealed the mechanism of Sijunzi decoction in the treatment of chronic gastritis.…”
Section: Introductionmentioning
confidence: 99%
“…In China, many therapies based on the theories of traditional Chinese medicine (TCM) have been considered. A recent systemic review has suggested that a Chinese classical formula, Sijunzi decoction, may benefit CAG patients [ 3 ]. In addition to Sijunzi decoction, Qinghuayin (QHY) is another Chinese formula that is widely used in the treatment of CAG based on the TCM theories of clearing heat and resolving dampness.…”
Section: Introductionmentioning
confidence: 99%